2019
DOI: 10.1016/j.jare.2018.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial role of bioactive lipids in the pathobiology, prevention, and management of HBV, HCV and alcoholic hepatitis, NAFLD, and liver cirrhosis: A review

Abstract: Graphical abstract Scheme showing possible role of HBV and HCV on cytokines, PUFA metabolism and development of hepatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 148 publications
0
19
0
Order By: Relevance
“…Despite the traditional view that AA is a substrate for pro-inflammatory eicosanoids, substantial evidence supports the concept that AA also serves as a precursor for a group of potent anti-inflammatory mediators. In addition to its ability to be transformed into the pro-inflammatory prostaglandin E2 and leukotrienes by cyclooxygenase (COX) and 5-lipoxygenase (LO), AA can also be transformed into lipoxins, resolvins, protectins, maresins, PGE1, and PGI2, which are found to represent a series of potent bioactive compounds that have been reported to have anti-inflammatory effects in chronic liver diseases, such as ALD, NAFLD, and cirrhosis (Das, 2019). Lactobacillus rhamnosus GG has been reported beneficial to ameliorating the reduction of AA induced by ethanol diet (Shi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the traditional view that AA is a substrate for pro-inflammatory eicosanoids, substantial evidence supports the concept that AA also serves as a precursor for a group of potent anti-inflammatory mediators. In addition to its ability to be transformed into the pro-inflammatory prostaglandin E2 and leukotrienes by cyclooxygenase (COX) and 5-lipoxygenase (LO), AA can also be transformed into lipoxins, resolvins, protectins, maresins, PGE1, and PGI2, which are found to represent a series of potent bioactive compounds that have been reported to have anti-inflammatory effects in chronic liver diseases, such as ALD, NAFLD, and cirrhosis (Das, 2019). Lactobacillus rhamnosus GG has been reported beneficial to ameliorating the reduction of AA induced by ethanol diet (Shi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, enhanced production of TNF-α and IL-6 seen during active COVID-19 also causes an EFAs (PUFAs) deficiency state due to their inhibitory action on desaturases ( 15 ). Hence, in order to bypass this block in the activity of desaturases and augment LXA4 formation supplementation of AA is needed that is known to enhance LXA4 with little or no change in PGE2 formation ( 32 , 33 , 34 , 35 ). In such an EFAs (PUFAs) deficiency state, AA supplementation results in inhibition of IL-6 and TNF-α synthesis, enhances the formation of LXA4 and suppresses PGE2 production and initiates the much-needed anti-inflammatory events and appropriate wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…There is reasonable evidence to suggest that inflammation, immune reactions, secretion of cytokines (both pro- and anti-inflammatory cytokines), resolution of inflammation, and restoration of homoeostasis are regulated by various BALs ( Figure 4 ) especially in the pathobiology of rheumatoid arthritis, atherosclerosis, diabetes mellitus, cancer, inflammatory bowel disease, lupus, and multiple sclerosis ( 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 16 , 25 , 31 , 33 , 34 , 35 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ). In fact, our studies revealed that in majority of these diseases, there is a deficiency of GLA, DGLA, AA, ALA, EPA and DHA) and LXA4 implying that altered levels of pro- and anti-inflammatory BALs (the balance being tilted more towards pro-inflammatory molecules) may account for their pathobiology suggesting that administration of AA and LXA4 could be of benefit in their resolution ( Table 1 , Table 2 , Table 3 , Table 4 , Table 5 , and Supplementary Tables 1–3 ).…”
Section: Introductionmentioning
confidence: 99%
“… 2 , 3 T2DM has become a major public health issue of global concern. 4 The pathogenesis of T2DM is complex and is influenced by genetic predisposition, inflammatory responses, insulin resistance, oxidative stress, and microcirculation abnormalities. 5 , 6 Inflammation can lead to insulin resistance and T2DM, while long-term inflammation can also aggravate hyperglycemia and promote the occurrence of diabetic complications.…”
Section: Introductionmentioning
confidence: 99%